Depiction of Mental Disorders in Human Behavior Through Cinema: Related to Ashoka Handagama’s Cinematic Approach - Wijayasinghe, A.; Rajapaksha, A. (Faculty of Graduate Studies, University of Kelaniya, Sri Lanka, 2016)
According to the Critics, cinema can be considered as the most powerful medium of art which can be used to deliver powerful messages towards the human society. In that aspect, the director of the film has a major responsibility in creating and delivering such messages to the audience through using creative elements of cinema. Most number of directors tries to reveal the unseen reality of human life through the cinema. Ashoka Handagama can be considered as a director who always tries to reveal the bitter truth of human nature through his cinematic approach. Most number of cinema creations done by Handagama created a controversial atmosphere in the Sri Lankan society. Some of his cinema creations were banned due to that reason. But Handagama tried to reveal some human mental disorders which prevailed in the Sri Lankan society where the public do not like to accept it. This research mainly focused on how Handagama tried to depict mental disorders of human nature through his cinematic approach. Content analysis and in-depth Interviews were used as the research methods to collect data regarding this. According to the data which was collected from the above methods, clearly suggest that number of mental disorders in human behavior had depicted through Ashoka Handagama’s cinematic approach. At the same time, these disorders have rally prevailed in the society where public do not like to accept that reality. In this context, Handagama’s cinema becomes controversial which paved the way for banning his films.
Keywords: Ashoka Handagama; Cinematic Approach; Mental Disorders; Cinema